Characteristics of patients transported by an air ambulance critical care team. Issue 5 (29th May 2012) - Catherall, Jacqueline A; Brown, Adam; Benger, Jonathan R
Abstract : Background: The aim of this study was to review patients conveyed by the Great Western Air Ambulance to its main receiving hospital. Methods: Retrospective data were collected for all patients transferred to Frenchay Hospital by the Great Western Air Ambulance between 1 June 2008 and 1 March 2010. Results: 115 patients were included in the review. Patients were conveyed up to 85 km, 79% bypassing the closest emergency department (ED). 51% of these patients had major trauma and 35% were intubated at the scene. On arrival, the mean time to CT scan was 78 min, reduced to 63 min for those with a head injury. 16% of patients were discharged from the ED. Conclusions: This review provides an overview of the characteristics of patients transferred to a major receiving hospital by a prehospital critical care team.